Hypoxic pretreatment of small extracellular vesicles mediates cartilage repair in osteoarthritis by delivering miR-216a-5p. (1st March 2021) - Rong, Yuluo; Zhang, Jiyong; Jiang, Dongdong; Ji, Chengyue; liu, Wei; Wang, Jiaxing; Ge, Xuhui; Tang, Pengyu; Yu, Shunzhi; Cui, Weiding; Cai, Weihua
Abstract: Osteoarthritis (OA) is a regressive joint disease that mainly affects the cartilage and surrounding tissues. Mounting studies have confirmed that the paracrine effect is related to the potential mechanism of mesenchymal stem cell (MSC) transplantation and that small extracellular vesicles (sEVs) play an imperative role in this paracrine signaling. In fact, hypoxia can significantly improve the effectiveness of MSC transplantation in various disease models. However, it remains unknown whether MSCs in the state of a hypoxic environment can enhance OA cartilage repair and whether this enhancement is mediated by sEV signaling. The primary aim of the present study was to determine whether sEVs from MSCs in the state of hypoxia (Hypo-sEVs) have a superior effect on OA cartilage repair relative to sEVs from MSCs in the normoxia (Nor-sEVs) state. By using an OA model and performing in vitro studies, we verified that Hypo-sEV treatment facilitated the proliferation, migration, and apoptosis suppression of chondrocytes to a greater extent than Nor-sEV treatment. Furthermore, we verified the functional role of sEV miR-216a-5p in the OA cartilage repair process. We also identified JAK2 as the target gene of sEV miR-216a-5p through a series of experiments. Our findings indicated that HIF-1α induces hypoxic BMSCs to release sEVs, which promote the proliferation, migration, and apoptosis inhibition of chondrocytes through the miR-216a-5p/JAK2/STAT3 signaling pathway. Therefore, hypoxic pretreatment is a prospective and effective method to maximize the therapeutic effect of MSC-derived sEVs on OA. Graphical abstract: Image, graphical abstract